Rhythm is it! you can change your life in a dance class - Stravinsky, Igor 1882-1971 (Boomtown Media, 2005)
The film accompanies three teenage protagonists in Berlin during the three-month rehearsals for a dance performance, choreographed by Royston Maldoom and accompanied by the Berliner Philharmoniker. There is Marie, who is still desperately trying to pass her secondary school leaving exams; Olayinka, who has recently arrived in Germany as a war-orphan from Nigeria; and Martin, who is battling to overcome his inhibitions. A sensitive and moving testimony to the power of dance and the raw talent of young people.
Enth. u.a.: Le sacre du printemps / von Igor' F. Stravinskij
Orig.: Deutschland 2004
Länge der Doku: 100 Min. - Länge der performance: 40 Min. - Making of und Ausschnitte aus weiteren Education-Projekten + Interviews: 52 Min. - Chronologie der Entstehung des Films + weitere Interviews: 38 Min. - Audiokommentare. - Einleitung zum "Sacre du printemps" durch Simon Rattle
Keywords: Rhythm is it! - You can change your life in a danceclass; Le sacre du printemps (Nijinskij); Dance -- Production and direction -- Germany -- Berlin; Dance -- Study and teaching -- Germany -- Berlin; Jugendsozialarbeit; Deutschland; Film; DVD-Video